Hydroxyapatite-Coated Titanium by Micro-Arc Oxidation and Steam–Hydrothermal Treatment Promotes Osseointegration - Wang, Xiaojun; Mei, Lina; Jiang, Xuesheng; Jin, Mingchao; Xu, Yan; Li, Jianyou; Li, Xiongfeng; Meng, Zhipeng; Zhu, Junkun; Wu, Fengfeng (Frontiers in Bioengineering and Biotechnology, 2021)
Titanium (Ti)-based alloys are widely used in tissue regeneration with advantages of improved biocompatibility, high mechanical strength, corrosion resistance, and cell attachment. To obtain bioactive bone-implant interfaces with enhanced osteogenic capacity, various methods have been developed to modify surface physicochemical properties of bio-inert Ti and Ti alloys. Nano-structured hydroxyapatite (HA) formed by micro-arc oxidation (MAO) is a synthetic material, which could facilitate osteoconductivity, osteoinductivity, and angiogenesis on Ti surface. In this paper, we applied MAO and steam-hydrothermal treatment (SHT) to produce HA-coated Ti hereafter Ti-M-H. The surface morphology of Ti-M-H1 was observed by scanning electron microscopy (SEM), and the element composition and roughness of Ti-M-H1 were analyzed by energy-dispersive X-ray analysis (EDX), X-ray diffractometer (XRD), and Bruker stylus profiler, demonstrating the deposition of nano-HA particles on Ti surfaces that were composed of Ca, P, Ti, and O. Then, the role of Ti-M-H in the osteogenesis and angiogenesis in vitro was evaluated. The data illustrated that Ti-M-H1 showed good compatibility with osteoblasts (OBs), which promoted the adhesion, spreading, and proliferation. Additionally, the secretion of ALP, Col-1, and ECM mineralization was increased by OBs treated with Ti-M-H1. Ti-M-H1 could stimulate ECs to secrete VEGF and promote the formation of capillary-like networks. Next, it was revealed that Ti-M-H1 also suppressed inflammation by activating macrophages, while releasing multiple active factors to mediate osteogenesis and angiogenesis. Finally, In vivo results uncovered that Ti-M-H1 facilitated higher bone-to-implant interface and was more attractive for the dendrites, which promoted osseointegration. In summary, MAO and SHT-treated Ti-M-H1 not only promotes in vitro osteogenesis and angiogenesis, but also induces M2 macrophages to regulate the immune environment, which enhances the crosstalk between osteogenesis and angiogenesis, and ultimately accelerates the process of osseointegration in vivo.